2022
DOI: 10.1371/journal.pcbi.1009972
|View full text |Cite
|
Sign up to set email alerts
|

Membrane contact probability: An essential and predictive character for the structural and functional studies of membrane proteins

Abstract: One of the unique traits of membrane proteins is that a significant fraction of their hydrophobic amino acids is exposed to the hydrophobic core of lipid bilayers rather than being embedded in the protein interior, which is often not explicitly considered in the protein structure and function predictions. Here, we propose a characteristic and predictive quantity, the membrane contact probability (MCP), to describe the likelihood of the amino acids of a given sequence being in direct contact with the acyl chain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 85 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…To generate the data set for training purposes, as shown in Figure A, we extracted 1362 nonredundant membrane protein structures and 7740 nonredundant soluble protein structures from the Protein Data Bank (PDB) and used FreeSASA to calculate the RASA of each residue . We then used MCP, as obtained from the MemProtMD database that was generated by massive coarse-grained (CG) molecular dynamics (MD) simulations, , to determine the RLA, RSA, and relative buried surface area (termed “RBSA”) of each residue with the following equations: RLA = MCP × RASA RSA = ( 1 MCP ) × RASA RBSA = 1 RASA = 1 RLA RSA Such a definition not only generates a quantity, RLA, which has the same dimension and physical meaning as RSA and RASA, but also accounts for the more complex nature of lipid molecules than water molecules in accessing the surface residues of proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To generate the data set for training purposes, as shown in Figure A, we extracted 1362 nonredundant membrane protein structures and 7740 nonredundant soluble protein structures from the Protein Data Bank (PDB) and used FreeSASA to calculate the RASA of each residue . We then used MCP, as obtained from the MemProtMD database that was generated by massive coarse-grained (CG) molecular dynamics (MD) simulations, , to determine the RLA, RSA, and relative buried surface area (termed “RBSA”) of each residue with the following equations: RLA = MCP × RASA RSA = ( 1 MCP ) × RASA RBSA = 1 RASA = 1 RLA RSA Such a definition not only generates a quantity, RLA, which has the same dimension and physical meaning as RSA and RASA, but also accounts for the more complex nature of lipid molecules than water molecules in accessing the surface residues of proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A residue is considered to be in direct contact with the hydrophobic core of membranes if its C α atom is within 6 Å of the lipid acyl chain atoms. In our recent study, we showed that 6 Å was indeed an appropriate cutoff value . The multichain proteins were split into single-chain sequences.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations